Ethnobotanical encyclopedia of cosmetic plants at Alwatzikhoebillah Palace as a biology learning resource - Riszka Septia; Mahwar Qurbaniah; Hanum Mukhti Rahayu (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Sambas Regency, West Kalimantan, has a rich cultural and biological heritage that can be utilized as a source of contextual learning. In the context of modern biology education, an approach that incorporates local potential and information technology is highly important. This study aims to develop learning media in the form of an ethnobotanical encyclopedia of cosmetic plants from the Alwatzikhoebillah Palace environment, intended as a biology learning resource for high school students. The research uses a Research and Development (R&D) method with a modified 4D model (Define, Design, Develop, Disseminate), excluding the dissemination stage. Data collection techniques include observation, interviews, and documentation. The encyclopedia was compiled based on the identification results of cosmetic plants through ethnobotanical studies and includes plant classification, morphology, active compounds, and usage methods. The media was developed using the Canva application and validated by experts in material, media, and language, and was tested on tenth-grade students at MAN 1 Sambas, West Kalimantan, through small- and large-scale questionnaires. The validation results showed that the encyclopedia was feasible for use, with a validity percentage of 92.86%, and the practicality assessment was categorized as very positive, with a percentage of 87.24%. It can be concluded that this ethnobotanical encyclopedia is suitable for use as a biology learning resource based on local potential.